Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1079/nrr200370
|View full text |Cite
|
Sign up to set email alerts
|

Food-frequency questionnaires: a review of their design, validation and utilisation

Abstract: A review of the literature concerning the design, utilisation and validation of food-frequency questionnaires (FFQ) has been carried out using a semi-systematic approach to obtaining, reviewing and extracting data from articles. Databases were searched from 1980 to 1999. The present review identified 227 validation (from 1980 to September 1999) and 164 utilisation (for 1998 only) studies. A number of design issues have been evaluated through the present review. These include: the need to consider how portion s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
461
5
30

Year Published

2009
2009
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 397 publications
(518 citation statements)
references
References 175 publications
22
461
5
30
Order By: Relevance
“…In the present study, the mean intake of energy and all macronutrients derived from food diaries was the same or higher compared with the QFFQ. Although a review of 227 validation studies by Cade et al (20) reported total fat as having the highest mean correlation coefficient among all nutrients, the present validation study indicated the highest correlation for carbohydrates (ICC 5 0?63, r 5 0?56).…”
Section: Discussioncontrasting
confidence: 72%
“…In the present study, the mean intake of energy and all macronutrients derived from food diaries was the same or higher compared with the QFFQ. Although a review of 227 validation studies by Cade et al (20) reported total fat as having the highest mean correlation coefficient among all nutrients, the present validation study indicated the highest correlation for carbohydrates (ICC 5 0?63, r 5 0?56).…”
Section: Discussioncontrasting
confidence: 72%
“…Finally, Bland-Altman plots enable assessment of the extent of variance in agreement and bias. Even though Bland-Altman plots are considered a gold standard in studies of methodical comparisons (18) , validation studies in nutritional epidemiology have only started to use this method during the past few years (27) . Finally, some limitations of our study need to be mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…FFQ are cost-effective tools to assess the usual current and past patterns of food intake over an extended period of time (37) . Estimates of the validity of our FFQ data, for Germany at least, were good, being in the same range as those reviewed by Willett (38) .…”
Section: Discussionmentioning
confidence: 99%